IMPLEMENTASI TERAPI OKUPASI MELALUI PELATIHAN KADER KESEHATAN JIWA DI POSYANDU JIWA KELURAHAN REJOMULYO KOTA KEDIRI - Dhita Kurnia Sari; Fajar Rinawati; Reni Nurhidayah; Riza Yuliawati; Erly Ermawati; Rismania Putri; Lingga Kusumawardani (Jurnal Abdi Masyarakat, 2025)
Mental health is an important aspect in maintaining the overall well-being of society. Posyandu jiwa is a form of health service that aims to provide support and intervention for individuals with mental health problems. However, the quality of Posyandu jiwa services is highly dependent on the competence of the cadres on duty. Therefore, training Posyandu jiwa cadres is an important strategy in improving the quality of services. This article aims to report on community service activities in the form of training for Posyandu jiwa cadres at Posyandu jiwa, Rejomulyo Village, with a focus on increasing the knowledge and skills of cadres in handling basic mental health. This training is expected to improve the quality of Posyandu jiwa services and encourage early detection and appropriate intervention for people with mental disorders in the community.